2022
DOI: 10.1038/s41598-022-24756-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between weight-adjusted-waist index and abdominal aortic calcification in adults aged ≥ 40 years: results from NHANES 2013–2014

Abstract: The negative effects of obesity on the cardiovascular health have drawn much attention. Weight-adjusted-waist index (WWI) has been proved to reflect weight-independent centripetal obesity. However, the association between WWI and abdominal aortic calcification (AAC) has not been reported before. Using data from National Health and Nutrition Examination Survey 2013–2014, we aimed to determine the relationship of WWI and AAC in adults aged ≥ 40 years. WWI was determined by dividing waist circumference by the squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…WWI was first used to better evaluate the morbidity and mortality of cardiovascular and metabolic diseases in the Korean population (25). Furthermore, trans-ethnic studies have revealed that WWI was positively associated with higher risks of hyperuricemia and multiple kinds of cardiovascular events, including heart failure, abdominal aortic calcification, and left ventricular hypertrophy (14,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…WWI was first used to better evaluate the morbidity and mortality of cardiovascular and metabolic diseases in the Korean population (25). Furthermore, trans-ethnic studies have revealed that WWI was positively associated with higher risks of hyperuricemia and multiple kinds of cardiovascular events, including heart failure, abdominal aortic calcification, and left ventricular hypertrophy (14,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first longitudinal study examining the relationship between WWI and newly diagnosed T2D. WWI has been explored in a wide range of fields, particularly those related to hypertension, albuminuria, hyperuricemia, left ventricular hypertrophy, and abdominal aortic calcification [ 10 , 11 , 12 ]. The results of these studies reinforce the effectiveness of WWI as a novel indicator of abdominal obesity to predict newly diagnosed T2D in rural China.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike BMI, which cannot distinguish between fat and muscle mass, WWI can better distinguish fat and muscle mass components and mainly reflects the problem of central obesity independent of body weight [ 9 ]. Cumulative evidence confirmed that the increasing value of WWI can be a useful risk factor for hyperuricemia, left ventricular hypertrophy, urinary albumin excretion, and abdominal aortic calcification [ 10 , 11 , 12 , 13 ]. However, the effect of WWI on the incidence of T2D has not been investigated before in rural Chinese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Waist circumference (WC) is another anthropometric index that also can be used to examine the risk of female infertility 26,27 . WWI (cm/√kg) was calculated as waist circumference in centimeters divided by the square root of weight in kilograms (WWI = WC/weight^2, WC in centimeters, weight in kilograms) 28,29 …”
Section: Methodsmentioning
confidence: 99%
“…26,27 WWI (cm/√kg) was calculated as waist circumference in centimeters divided by the square root of weight in kilograms (WWI = WC/weight^2, WC in centimeters, weight in kilograms). 28,29…”
Section: Assessment Of Wwimentioning
confidence: 99%